(untitled) (gjstudies, 2020)
The landscape of internal audit functions within large enterprises has undergone significant transformation over the past two decades, with outsourcingemerging as a strategic consideration for organizations seeking to balancecontrol, expertise, and cost efficiency. While previous research has examinedinternal audit outsourcing through primarily economic lenses, this study introduces a more comprehensive framework that integrates regulatory, technological, and strategic dimensions. The increasing complexity of regulatoryenvironments, particularly following the implementation of legislation suchas the Sarbanes-Oxley Act, has fundamentally altered the calculus behindinternal audit sourcing decisions. Simultaneously, the rapid advancementof audit technologies and the emergence of new risk domains including cybersecurity and artificial intelligence governance have created both pressuresand opportunities that influence organizational approaches to internal auditresourcing